Evaluation of different phenotypic tests for detection of metallo-β-lactamases in imipenem-resistant Pseudomonas aeruginosa - Sachdeva, Rohit (J Lab Physicians, 2017)
PURPOSE: Pseudomonas aeruginosa causes a wide spectrum of infections including bacteremia, pneumonia, urinary tract infection, etc., Metallo-beta-lactamase (MBL) producing P. aeruginosa is an emerging threat and cause of concern as they have emerged as one of the most feared resistance mechanisms. This study was designed to know the prevalence of MBL production in P. aeruginosa and to evaluate the four phenotypic tests for detection of MBL production in imipenem-resistant clinical isolates of P. aeruginosa. METHODS: Totally, 800 isolates of P. aeruginosa isolated from various clinical samples were evaluated for carbapenem resistance and MBL production. All imipenem-resistant strains were tested for carabapenemase production by modified Hodge test. Screening for MBL production was done by double-disc synergy test and combined disc test (CDT). Confirmation of MBL production was done by the E-test (Ab BioDisk, Solna, Sweden). RESULTS: Out of the 800 isolates of P. aeruginosa, 250 isolates were found resistant to imipenem. Based on the results of E-test, 147 (18.37%) isolates of P. aeruginosa were positive for MBL production. The CDT has the highest sensitivity and specificity for the detection of MBL production as compared to other tests. CONCLUSION: The results of this study are indicative that MBL production is an important mechanism of carbapenem resistance among P. aeruginosa. Use of simple screening test like CDT will be crucial step toward large-scale monitoring of these emerging resistant determinants. Phenotypic test for MBL production has to be standardized, and all the isolates should be routinely screened for MBL production.